1975
DOI: 10.1136/oem.32.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of asbestos on lipid peroxidation in the red cells.

Abstract: Effect of asbestos on lipid peroxidation in the red cells. In vitro exposure of red cells to five International Union against Cancer (UICC) standard reference asbestos samples resulted in an increase of thiobarbituric acid substances. Chrysotiles developed the largest amounts of lipid peroxides, followed by anthophyllite, amosite, and crocidolite in decreasing order. Compared with the control samples, erythrocytes free of dusts, all types of the asbestos examined disclosed significant differences. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…
The initial event after inhalation of quartz particles is their damaging effect on macrophages, which represent hte most critical cells involved in the pathogenesis of silicotic fibrosis (1,ll). Our previous studies (4,5,6,7,8,9), documented also by other authors (2,3,10,14) provided support for the assumption that lipid peroxidation may be one of the quartz cytotoxic mechanisms in cells and lung tissue. There is evidence that a cooperative antioxidative defense system located within the biological structures can protect against cellular peroxidative damage (12,13).
…”
supporting
confidence: 79%
“…
The initial event after inhalation of quartz particles is their damaging effect on macrophages, which represent hte most critical cells involved in the pathogenesis of silicotic fibrosis (1,ll). Our previous studies (4,5,6,7,8,9), documented also by other authors (2,3,10,14) provided support for the assumption that lipid peroxidation may be one of the quartz cytotoxic mechanisms in cells and lung tissue. There is evidence that a cooperative antioxidative defense system located within the biological structures can protect against cellular peroxidative damage (12,13).
…”
supporting
confidence: 79%
“…In previous studies asbestos has been shown to induce lipid peroxidation with red blood cells (Gabor & Anca, 1975), phospholipid emulsions (Weitzman & Weitberg, 1985) and isolated microsomes (Gulumian et at., 1983). Others have shown the iron component of crocidolite fibres can catalyse the generation of hydroxyl radicals from hydrogen peroxide (Weitzman & Graceffa, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Gabor and Anca (54) first demonstrated that asbestos can initiate lipid peroxidation in a cell model of red blood cells. Gulumian et al (55,56) showed that crocidolite asbestos enhanced lipid peroxidation in rat lungs and liver microsomes.…”
Section: Eaizymesmentioning
confidence: 99%